Building Culturally and Linguistically Sustaining Spaces for Emergent Bilinguals: Using Read‐Alouds to Promote Translanguaging - Osorio, Sandra Lucia (The Reading teacher, 2020)
Multilingual students arrive in classrooms with rich language knowledge and funds of knowledge. Educators must recognize that emergent bilinguals speak multiple languages. They have one unitary language system; their language is bilingualism. Whether in a monolingual classroom setting or a multilingual setting, when working with emergent bilinguals, it is important that all of the students’ linguistic resources are welcomed into the classroom. The author describes how, as a first‐grade dual‐language (Spanish–English) teacher, she used children's literature and translanguaging to support her emergent bilinguals in using all of their linguistic resources to make meaning and build a linguistically sustaining space. The use of the text created a space for the teacher to model translanguaging and for the students to use all of their linguistic resources.